Species Composition and Growth Pattern of a Multi-Species Grouper in Kwandang Bay, Sulawesi Sea, Indonesia - Dewi Shinta Achmad; Muh Saleh Nurdin; Fauziah Azmi; Merita Ayu Indrianti; Evi Hulukati; Jamaluddin Jompa; Teuku Fadlon Haser; Novianita Achmad (Faculty of Fisheries and Marine Universitas Airlangga, 2023)
Highlight Research There are 26 species identified to be originated from the bay, which the highest diversity in Indonesia Six species found in Kwandang Bay is showing trends of decreasing populations and two species vulnerable based on IUCN conservation list Growth model and Fulton condition factor determined for 14 species indicates that they live in a good state of well beings in the bay The models and condition factors also reflect the adequate food resources required for grouper growth which makes Kwandang Bay as a good habitat for groupers Abstract Grouper fishery has been the source of income for 3,700 fishermen in Kwandang Bay. Since 2017, grouper populations in Kwandang have been depleting due to the absence of management. This research aimed to analyze species composition, length-weight relationship, and condition factor of the groupers. Samples were collected from fishers who caught the fish using traps, speargun, and handline. Samples were identified through a method by Heemstra and Randall, while the length-weight relationship was estimated using log-linear regression and t-test. The number of specimens identified during January - December 2021 was 1,571 individuals. Research showed that those samples consisted of 26 species under eight genera. Six species found in Kwandang Bay were showing trends of decreasing populations and two species were vulnerable based on the IUCN conservation list. Length-weight relationship analysis of 14 grouper species resulted in b value ranging from 1.6359 to 3.4417 and R2 ranges from 0.7718 to 0.9858. A significant test at a 95% confident interval showed that 14 species had an isometric growth pattern. Fulton condition factors show that Kwandang Bay is an essential habitat for groupers, and the bay can support the fish growth due to the adequate food availability.